Relationship of monalonion velezangeli carvalho and amp; costa (hemiptera: miridae) with the phenology of avocado (persea americana mill., cv. hass) / relación de monalonion velezangeli carvalho and amp; costa (hemiptera: miridae) con la fenología del aguacate (persea (2012)
Monalonion velezangeli is considered one of the most harmful pests of avocado cv. Hass, as far as it attacks vegetative buds, flowers and fruits during all the productive stages of the crop. This situation is aggravated by the lack of knowledge on insect preferences and their relationship with crop phenology. As a contribution to the management of this insect, we studied the relationship between plant phenology and the presence of M. velezangeli, as well as its preferences across tree strata and structures. Data were obtained from six orchards located in the Colombian departments of Antioquia, Caldas and Quindío. After randomly selecting 20 trees at each orchard, 12 branches were marked on each tree, covering the combinations of the four cardinal points with three plant strata (low, medium and high). During a period of 12 months, each branch was monitored by recording its phenological stage (vegetative, flowering and fruiting), the number of individuals of M. velezangeli and the presence of fresh damages on it. An analysis of variance determined that the presence of the insect and its damage were more abundant on the flowering and fruiting branches than on the vegetative ones, as well as in the medium and upper strata of the trees. The damage caused by M. velezangeli was observed to be significantly higher in the reproductive structures (flowers and fruits) as compared to the vegetative structures. / Monalonion velezangeli es considerada una de las principales plagas del aguacate cv. Hass en Colombia, debido a que ataca brotes vegetativos, flores y frutos, durante todas las etapas productivas del cultivo. Esta situación se ve agravada por el desconocimiento de las preferencias del insecto, así como de su relación con la fenología de la planta. Como un aporte al manejo de este insecto, se estudió la relación entre la fenología de la planta y la presencia de Monalonion, así como sus preferencias por estructura y estrato. Las observaciones se hicieron en seis huertos ubicados en los departamentos de Antioquia, Caldas y Quindío (Colombia). Se eligieron 20 árboles por finca; en cada uno, se marcaron 12 ramas que correspondían a las combinaciones de los cuatro puntos cardinales en tres estratos (bajo, medio y alto). En la rama seleccionada se registró, durante 12 meses, su estado fenológico (vegetativo, floración o fructificación), el número de individuos de M. velezangeli y los daños frescos presentes. Mediante análisis de varianza, se determinó que la presencia del insecto, así como su daño fueron mayores sobre las ramas en floración y fructificación y en los estratos alto y medio de los árboles. El daño causado por M. velezangeli fue significativamente mayor en las estructuras reproductivas (flores y frutos) en relación con las estructuras vegetativas.